2021
DOI: 10.3390/su13169018
|View full text |Cite
|
Sign up to set email alerts
|

Policy Considerations for African Food Systems: Towards the United Nations 2021 Food Systems Summit

Abstract: Achieving food and nutrition security and ending hunger is a complex and multi-faceted global challenge, which requires urgent attention, particularly in Africa. To eliminate hunger, the continent needs to transition to new sustainable, inclusive, and resilient food systems that deliver nutritious food and a healthy planet for all. This paper discusses challenges and opportunities highlighted during the “Food Systems Transformation to Address the SDGs” session convened by the African Research Universities Alli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…Many indigenous or traditional crops remain undocumented, and the documented few have not been fully exploited (Sibanda & Mwamakamba, 2021). Reoriented research will provide an opportunity to record undocumented indigenous crops to unleash their market and commercialization potential.…”
Section: Discussionmentioning
confidence: 99%
“…Many indigenous or traditional crops remain undocumented, and the documented few have not been fully exploited (Sibanda & Mwamakamba, 2021). Reoriented research will provide an opportunity to record undocumented indigenous crops to unleash their market and commercialization potential.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, advances in aeration and preservation technologies, inventive packaging, biowax coating, effective pulse processing technology, and the creation of cool stores are all contributing to increases in food access (Fedotova, 2021). The use of advanced cleaning, grading, and packing techniques, low-cost refrigerated vehicles, low-cost solar dryers, and vacuum or hermetic sealing systems can signi cantly increase food access in several African nations (Sibanda & Mwamakamba, 2021).…”
Section: Knowledge Based Scm and Food Securitymentioning
confidence: 99%
“…Food insecurity and hunger are increasing globally, with above 30 percent of the worldwide population presently facing food insecurity (Sibanda and Mwamakamba, 2021). Food and Agriculture Organization of United Nation FAO (2021) reported that about 927.6 million people suffered food insecurity in diverse and several periods in 2020.…”
Section: Introductionmentioning
confidence: 99%